Kelayakan Bahan Ajar Materi Perbandingan Trigonometri yang Berorientasi Hots pada Siswa SMA - Fahrur Rosyi; Achmad Noor Fatirul; Hartono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
This research aims to determine the feasibility of the development of teaching materials math trigonometry comparative material for high school students. Facts on the ground show that the study of mathematics, especially trigonometry matter of learning outcomes is not maximized, be it about the response of students and student learning activities. This is due to lack of instructional materials interesting and easily understood by students, especially trigonometry comparison material. In designing these materials, researchers used a Dick and Carey model of development that has been modified. The results of the validation test found thatOverall subject matter experts provide an assessment of the average score of 4.15. Media experts provide an assessment of the average score of 4.23. student questionnaire responses (test small groups) receive an average score of 4.68 so that the overall teaching materials can be categorized as very feasible.